1997
DOI: 10.1538/expanim.46.89
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rat Serum Alkaline Phosphatase Isoenzyme by means of Wheat Germ Agglutinin.

Abstract: Abstract:Wheat germ agglutinin (WGA) precipitates bone type serum alkaline phosphatase (sALP) isoenzyme specifically. The precipitates are composed of the macromolecules of WGA and "bone type sALP" (WGA-ALP complex). In order to use bone type sALP as a marker in polyacrylamide gel electrophoresis (PAGE), a method to separate "bone type sALP" from the "WGA-ALP complex" was established by using N-acetyl-Dglucosamine (GlcNAc)-Sepharose 6B column chromatography. It was concluded that this method is useful for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…We previously reported that one of the serum isoenzymes disappeared under fasting conditions [17]. In addition, this particular isoenzyme was identified as one of the isoenzymes observed in the intestine intrinsically [18]. The physiological role of ALP in the intestine is not thoroughly understood.…”
Section: Introductionmentioning
confidence: 97%
“…We previously reported that one of the serum isoenzymes disappeared under fasting conditions [17]. In addition, this particular isoenzyme was identified as one of the isoenzymes observed in the intestine intrinsically [18]. The physiological role of ALP in the intestine is not thoroughly understood.…”
Section: Introductionmentioning
confidence: 97%